SOCIAL STYLES OF ONLINE LEARNERS IN GENERAL ENGLISH COURSE : A SURVEY IN THREE CLASSES IN A PRIVATE HIGHER EDUCATION INSTITUTIONS IN BANDUNG, INDONESIA - Arni Sukmiarni (Jurnal Sastra - Studi Ilmiah Sastra, 2021)
This paper is a report of a survey on identifying social types of online leaners taking General English as an obligatory course in three classes in a private universities. The aim of this study is to identify learners’ social types when they are involving in learning activities in online learning. Research data are gained by distributing a survey to eighty-eight online learners. The data was analyzed quantitavely and categorized into the social styles from Grasha-Riechman Student Learning Style Scales. The result indicates that the learners’s social styles prefer to be more dependent, collaborative and participative in online learning.